Technical, Environmental and Economic Feasibility study of installing a Photovoltaic Power Plant on a Landfill in SouthWestern Sweden - Ramesh, Varun Gowda Palahalli (My University, 2020)
The increasing global energy demand, which is today mainly supplied by energy sources that are of fossil origin has a severe impact on the environment. Renewable energy sources have the potential to mitigate emissions and are being promoted globally as well as nationally in Sweden. Solar power production has been increasing in the past decade due to increased deployment in countries such as the USA, China, India, and the rest of the world driven by climate targets. But the land requirement will put a constraint on how much PV can be deployed. Hence, there is a need to explore the possibility of establishing a photovoltaic plant on land spaces that have limited applications such as closed landfill sites. This study explored such possibility by researching technical challenges and solutions and conducting a Life Cycle Assessment and an economic feasibility analysis on establishing the solar photovoltaic plant on a closed landfill at kikås, Mölndal. The research on technical challenges revealed that several challenges could arise during the installation phase depending on the condition of the landfill site. A major challenge lies with the mounting system (a type of anchoring used to erect the mounting system) due to limitations placed by ground penetration restrictions and risks of damaging the settlement. Hence, possible solutions have been identified and described in this study. A cradle to grave life cycle assessment has been made using OpenLCA software empowered by the ecoinvent database. The results from this study show that the GWP of 75.16 gCO2- eq./kWh for a PV system is situated in the area with irradiation around 1000 KWh/yr. A major portion of that arises from production and transportation of solar modules which is equal to 56.7 gCO2- eq./kWh which is 75.48% of the total GWP arising from the PV plant. Besides the GWP, the acidification potential was found to be 0.401 gSO2 eq./kWh. Economic feasibility is assessed by modeling the electricity prices based on two different (2015 and 2018) historical electricity price profiles which are used for revenue calculation. Based on the four scenarios with different electricity profiles it was observed that the revenue will be higher in the case when the electricity price profile follows a similar trend of 2018.
Keywords: Photovoltaic; Life Cycle Assessment (LCA); landfill; landfill cap; Environmental impcat; landfill settlements; Mounting techniques